-10+7t=-3t-10

Simple and best practice solution for -10+7t=-3t-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10+7t=-3t-10 equation:


t in (-oo:+oo)

7*t-10 = -3*t-10 // + -3*t-10

7*t-(-3*t)-10+10 = 0

7*t+3*t-10+10 = 0

10*t = 0 // : 10

t = 0

t = 0

See similar equations:

| -16x^2-8x-1=0 | | -7b+1=5b+61 | | 4b-1=-25+6b | | 7w+5=6w+6 | | 4+7d=-d+4 | | -3+7b=-5b+81 | | x+6=-24+4x | | -5w-9=23+3w | | 24x^2-1= | | 5a+1=-23+7a | | m-10=-3+2m | | 2k+2=-7k-25 | | -7t+9=75+4t | | t+2=6t-33 | | 5b-2=-2+2b | | 3k+3=7+k | | 5=4x-3x | | -10x^2-12x+16=0 | | 5b+10=-b+58 | | -2a-3=5-4a | | 2b+5=6b+53 | | 6d+2=-79-3d | | 10+6a=3a+46 | | -6-3d=4d-69 | | 2k+3=-9+6k | | 6k+10=k-50 | | 5w+9=-3w+1 | | 9-6k=-7k+16 | | m+2=6m-58 | | 4t-10=-32+6t | | 2+6a=5a-9 | | 25x^2+25+6=0 |

Equations solver categories